PENGARUH SOSIOLOGI KRITIS, KEATIFITAS, MENTALITAS TERHADAP PENDIDIKAN AKUNTANSI PADA MAHASISWA AKUNTANSI FEB UNISMA Angkatan 2014 - Nurjannah Nurjannah; Noor Shodiq Askandar; Junaidi Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2018)
ABSTACTIONThe study aims to examine the effect of critical sociology, creativity,mentality on accounting education on accounting students of the 2014 IslamicUniversity of Malang Faculty of Economics and Business. The population in thisstudy were accounting students. The sampling technique in this study usespurposive sampling method. The type of data used is primary data with themethod of collecting data distributing questionnaires. The analytical tool used ismultiple linear regression.The results showed that simultaneously and partially critical sociology,creativity, mentality had a positive and significant effect on accounting educationfor accounting students of the 2014 Islamic University of Malang Faculty ofEconomics and Business.Keywords: Critical Sociology, Creativity, Mentality